The soil microbial methylome: a tool to explore the role of epigenetic memory in driving soil abiotic legacy effects - Sizmur, Tom; Larionov, Alexey (Elsevier, 2025)
Epigenetics is a phenomenon whereby a stable hereditable change in gene expression can occur without changing the DNA sequence. DNA methylation (the addition of a methyl group to specific nucleotides in specific DNA motifs) is the most studied epigenetic mechanism and is widely observed in both eukaryotic and prokaryotic cells. We hypothesise that the soil methylome may play an important role in the manifestation of soil abiotic legacy effects, whereby temporary exposure of soil microbial communities to particular environmental conditions influences future soil microbial function. These abiotic legacy effects are important because they underpin the delivery of key ecosystem services in response to global environmental change. Third generation long-read sequencing technologies, such as Pacific Bioscience Single-Molecule Real-Time sequencing (SMRT-seq) and Oxford Nanopore sequencing provide an opportunity to study methylome heterogeneity in complex microbial communities. The simultaneous measurement of epigenetic, transcriptional, and microbial community composition changes may lead to the development of biomarkers of historic environmental stress and a greater understanding of the role of the soil methylome in the resilience of soil microbial communities to future environmental perturbations. It is therefore timely to add the meta-epigenetic layer to the multi-omics analysis of the soil microbiome to advance our understanding of soil abiotic legacy effects.
Keywords: 41 Environmental Sciences; 4106 Soil Sciences; Genetics; Human Genome; Nanotechnology; Bioengineering; 2.1 Biological and endogenous factors; Agronomy & Agriculture; Microbial epigenetics; DNA methylation; Methylome; Legacy effects; Perturbations; Meta-epigenetics; Long-read sequencing